Design of Pouring Stand with Adjustable Pouring Height for Metal Moulding Flask in Green Sand-Casting Application - MUSTAPA KAMARUL BASAH, MUQRI; Saleh, Aslinda (Progress in Engineering Application and Technology, 2021)
Casting process had been made long ago, and effectively performing this process was tremendously influential on their gain of power during the Bronze Age. The process gone through many improvements from time to time until the new technology such as investment casting, stir casting, vacuum casting and others. However, sand casting which is the ancient and conventional casting method still valid to be used till today due to its advantages. Porosity is one of the issues in alloy castings, it can be formed either from the process, materials or other factor. The main aim for this paper is to design a pouring stand with adjustable pouring heights for metal moulding flask in green sand casting application. The design is focusing on reducing the turbulence that produce bubble that later will become a defect in casting by determine the specific height which is 10 cm, 15 cm, and 20 cm. Based on the result, the comparative between design I and design I show that design II is more compactible for the use of the adjustable stand.The design of the adjustable stand has been done using SOLIDWORK software and the same design is analyzed using SOLIDWORK software simulation. The analysis for the design showed yellow coloured stress distribution at the ladle holder/cup at the V-shape design II with the value of 2.045e+03 N/m² to 2.249e+03 N/m². Thus, design II showed better distribution with lower value than design I of stress that considered as high. The analysis also is analyzed using costing analysis to corroborate the conclusions arrived at through cost analysis. The cost of the best adjustable pouring height stand design II (V shape) with ladle holder feature is RM 1117.76. Based on the result, it is revealed that design II is the most optimum design of pouring stand with adjustable pouring height for metal moulding flask in green sand casting application.